2009 24th Annual IEEE Conference on Computational Complexity 2009
DOI: 10.1109/ccc.2009.21
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-Polynomial Size Circuit Bounds

Abstract: Abstract-InWe explore questions about fixed-polynomial size circuit lower bounds around and beyond the algebrization barrier. We find several connections, including• The following are equivalent:where ONP is the class of languages accepted obliviously by NP machines, with witnesses for "yes" instances depending only on the input length.• For a large number of natural classes C and all k 1, C is in SIZE(n k ) if and only if C/1 ∩ P/poly is in SIZE(n k ).• If there is a d such that MATIME(n) ⊆ NTIME(n d ), then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…This notion has been studied before: Chakaravarthy and Roy [16] and Fortnow and Santhanam [17] defined the complexity class ONP ('Oblivious NP'), which is like NP except that the witness can depend only on the input length. Independently, Aaronson [5] defined the complexity class YP, 6 which is easily seen to equal ONP ∩ coONP.…”
Section: Theorem 15 ([10])mentioning
confidence: 99%
“…This notion has been studied before: Chakaravarthy and Roy [16] and Fortnow and Santhanam [17] defined the complexity class ONP ('Oblivious NP'), which is like NP except that the witness can depend only on the input length. Independently, Aaronson [5] defined the complexity class YP, 6 which is easily seen to equal ONP ∩ coONP.…”
Section: Theorem 15 ([10])mentioning
confidence: 99%
“…But does every set in N P ∩ P/poly have such universal NP-witnesses? Denoting the class of sets having input-oblivious NP-proofs by ON P, Fortnow et al [6] showed that Theorem 1.1 (on the power of input-oblivious NP-proofs [6]):…”
Section: Soundnessmentioning
confidence: 99%
“…While the first part of this note is devoted to surveying the input-oblivious aspect of the work of Fortnow et al [6], in the second part we define and study input-oblivious versions of various forms of probabilistic pproof systems. In particular, we consider input-oblivious versions of interactive proof systems (i.e., IP), zero-knowledge proof systems (i.e., ZK), and probabilistically checkable proof systems (i.e., PCP).…”
Section: Other Input-oblivious Proof Systemsmentioning
confidence: 99%
See 2 more Smart Citations